Survey on Major Diseases of Chaba (Piper chaba) - , M.R. Islam, M. S. U. Khan, F. A. Nasim, S. Hasan, M. A. Rahman, S. Sultana, N. Aktar (Archives of Current Research International, 2024)
Chaba plants, belonging to the Piperaceae family, are susceptible to several diseases. It has become more vulnerable to disease infection due to the climate change. A comprehensive survey was undertaken from July 2021 to July 2022 in Khulna, Bagerhat, Jashore, Chuadanga, and Magura to identify the major diseases that affect chaba production. The research was conducted in farmers' fields, specifically focusing on 5 different areas where Chaba was cultivated predominantly. The survey identified four diseases, namely foot and root rot, leaf rot, leaf spot, and leaf rust, as important diseases in these areas, based on their occurrence. Dumoria, Khulna has the highest disease incidence. The disease incidence varied between 7.33% and 16.73%. Dumoria upazilas had the highest occurrence of foot and root rot (15-25%) as well as leaf rot (20-30%). While, Alomdanga upazila had the lowest incidence of foot and root rot (10-15%) and leaf rot (10-15%). The farmers in these regions consider these diseases to be a significant risk to the future cultivation and extension of Chaba in the southern portion of Bangladesh.